Climate variability drives population cycling and synchrony. Issue 4 (6th February 2017) - Pomara, Lars Y.; Zuckerberg, Benjamin
Abstract: Aim: There is mounting concern that climate change will lead to the collapse of cyclic population dynamics, yet the influence of climate variability on population cycling remains poorly understood. We hypothesized that variability in survival and fecundity, driven by climate variability at different points in the life cycle, scales up from local populations to drive regional characteristics of population cycling and spatial synchronization. Location: Forest in the US Upper Midwest and Great Lakes region. Methods: We tested hypotheses linking variation in vital rates of Ruffed Grouse ( Bonasa umbellus ), a declining species that displays decadal population cycles, to temperature and precipitation anomalies and land use intensity, using rate estimates from multiple locations in eastern North America. We used climate‐demographic linkages to simulate spatially explicit population dynamics from 1982 to 2069, evaluated predictions against monitoring data and assessed predicted population dynamics under future climate projections. Results: Nest success and winter survival were linked to temperature and precipitation anomalies, and demographic models explained important spatio‐temporal characteristics of cycling and synchrony in monitoring data. The climate‐driven vital rates were necessary for cycling and synchrony in models, even though the four included climate variables were not individually periodic. Cycling and synchrony were stronger at more northerly latitudes, but this transition occurred abruptly, reflecting regional variation in winter conditions. Forecasts suggested climate‐driven cycling through mid‐century, followed by desynchronization and dampening. Main conclusions: Climate variability can drive spatio‐temporal variation in demographic rates, and population cycling can result from these relationships. Pathways linking climate to broad‐scale population dynamics involve responses of vital rates to several climate variables at different times of year and may be more complex than direct responses to known modes of climate variability. The wide‐ranging impact of climate change on the demographics of northerly adapted species has the potential to degrade patterns of population synchrony and cycling.